Up-Converting Luminescence and Temperature Sensing of Er3+/Tm3+/Yb3+ Co-Doped NaYF4 Phosphors Operating in Visible and the First Biological Window Range - Jingyun Li; Yuxiao Wang; Xueru Zhang; Liang Li; Haoyue Hao (Nanomaterials, 2021)
Accurate and reliable non-contact temperature sensors are imperative for industrial production and scientific research. Here, Er3+/Tm3+/Yb3+ co-doped NaYF4 phosphors were studied as an optical thermometry material. The typical hydrothermal method was used to synthesize hexagonal Er3+/Tm3+/Yb3+ co-doped NaYF4 phosphors and the morphology was approximately rod-like. The up-conversion emissions of the samples were located at 475, 520, 550, 650, 692 and 800 nm. Thermo-responsive emissions from the samples were monitored to evaluate the relative sensing sensitivity. The thermal coupled energy level- and non-thermal coupled energy level-based luminescence intensity ratio thermometry of the sample demonstrated that these two methods can be used to test temperature. Two green emissions (520 and 550 nm), radiated from 2H11/2/4S3/2 levels, were monitored, and the maximum relative sensing sensitivities reached to 0.013 K−1 at 297 K. The emissions located in the first biological window (650, 692 and 800 nm) were monitored and the maximum relative sensing sensitivities reached to 0.027 (R692/650) and 0.028 K−1 (R692/800) at 297 K, respectively. These results indicate that Er3+/Tm3+/Yb3+ co-doped NaYF4 phosphors have potential applications for temperature determination in the visible and the first biological window ranges.